Chapter Telling Transversal Competences... to be Professionally Promoted - Capo, Marianna (Studies on Adult Learning and Education, 2018)
This article introduces experimental reflection on the experiences at an 'Employability Skills' laboratory of a group of young volunteers from the National Civilian Service under the 'Support and Inclusion' project of the Employment Promotion Section (SPO in Italian) of the University of Naples Federico II SInAPSi Centre. Young volunteers were included as unstructured support figures in activities that sought mainly to assist and serve students with disabilities. More specifically, these activities included: accompaniment and support during lessons; digitization of teaching material; providing support for the assorted services offered by the University Centre; general training implemented by AMESCI staff; specific training implemented by SInAPSi operatives. The experiences, which were accomplished in cooperation with the Europe 2020 programme, included the creation of an integrated system to recognize and validate formal, non-formal, and informal skills, as a tool to promote youth employment (Striano, Capobianco 2016)